Visualization tools for visual impact assessments: a study of immersive technologies - DePriest, Anthony J. (Kansas State University, 2018)
Visual Resource Management practices are relatively new, dating back to the late 1960’s and early 1970’s (Litton, 1984; USDA Forest Service, 2010). At the conception of visual resource management practices, computers were not prominent in everyday life. As computing tools advanced along with easier access to technology, a perceived surge of research emerged within the VRM field in the 1990’s. Since that time, it appears that few landscape architects have continued to research how modern technological advancements, specifically the recent expansion of virtual reality, could be used in predicting the visual impacts of proposed development. This report aims to compare virtual environments to existing methods for assessing the visual impacts of development in the Texas prairie ecoregion. New reliable tools at the hands of experts could lead to more accurate and more understood consequences of development on the visual landscape. Following precedents set forth in similar research studies, participants will view photographic and rendered images of scenes before and after development projected through a digital display. Potential development will be analyzed through a comparison analysis in which multiple visualization methods (Google Earth and photo sphere images) are compared to industry standards of two-dimensional images and renderings. The comparison analysis will survey experts and ask them to rate certain views before and after development through multiple visualization methods. Results from the study show a high similarity in perceived impacts between 2D images and Google Earth assessments. However, photo sphere images were rated consistently lower than their counterparts. Image resolution and detail could have led to the lower ratings in photo sphere images. Overall, participants felt that immersive visualization media will soon replace the use of 2D images for conducting visual impact assessments.
Keywords: Visual impact assessment; Visual resource